Implementation of Rawa Buntu Station Development Into a Transit Oriented Development (TOD) Station - Trisnawati, Anggita (Blantika: Multidisciplinary Journal, 2026)
Public services are the responsibility of the government and are carried out by government agencies to meet community needs in various sectors, so that the services provided can be affordable, easy, fast, and efficient. One government effort to improve services is the development of train stations based on Transit Oriented Development (TOD) by Perumnas in collaboration with PT KAI as a solution to improve mobility efficiency and reduce dependence on private vehicles. This study aims to analyze the implementation of the TOD concept at Rawa Buntu Station as an effort to realize an integrated, environmentally friendly, and public-transportation-oriented urban area. The research used is descriptive with a qualitative approach. The focus of this research is based on the policy implementation model proposed by George C. Edward III. The findings reveal that communication indicators remain suboptimal due to the absence of regular socialization and education regarding TOD development. However, resources are adequately utilized in accordance with assigned authorities, and Perumnas Mahata Serpong demonstrates strong commitment and support for Regional Regulation No. 9 of 2019. Furthermore, the bureaucratic structures of both Perumnas and PT KAI have implemented Standard Operating Procedures (SOPs) properly. Rawa Buntu Station has the potential to serve as a model for sustainable TOD development in urban areas.